2022
DOI: 10.1002/fut.22388
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and tail risk contagion across commodity futures markets

Abstract: This paper examines the impact of COVID-19 on tail risk contagion across commodity futures markets using a copula-based network method. We document a significant increase in the lower and upper tail contagiousness of commodities following the COVID-19 outbreak. Contagion shows an obvious clustering characteristic, that is, there is higher tail risk connectedness between commodities in the same category. Agricultural commodities are significantly less contagious than metals and energy commodities; soft commodit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The empirical results are consistent with other studies that focus on commodities (see Figure A3 and Tables A11 and A12 in the appendix). Agricultural commodity prices are least affected by the COVID‐19 pandemic (Elleby et al, 2020; Qiao & Han, 2022). This is mainly because the demand for the most basic agricultural commodities is relatively sustained and most agricultural commodities are available in stock, which ensures the stability of supply and prices (Cariappa et al, 2022; Hobbs, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The empirical results are consistent with other studies that focus on commodities (see Figure A3 and Tables A11 and A12 in the appendix). Agricultural commodity prices are least affected by the COVID‐19 pandemic (Elleby et al, 2020; Qiao & Han, 2022). This is mainly because the demand for the most basic agricultural commodities is relatively sustained and most agricultural commodities are available in stock, which ensures the stability of supply and prices (Cariappa et al, 2022; Hobbs, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There exists a bidirectional asymmetrical relationship between crude oil markets and agricultural commodity markets, exacerbated during financial crises, the COVID-19 pandemic, and oil market crashes [6][7]. COVID-19 has had significant and enduring impacts on the risk interdependence between energy, agriculture, and other commodities [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, the research on financial risk contagion and spillover is mainly discussed from three aspects: extreme risk, return and volatility spillovers (Chatziantoniou et al, 2022;Gong, Zhao, et al, 2023;Qiao & Han, 2023). For example, Wang et al (2018) used the TENET model to construct an extreme risk spillover network among financial institutions in China, and found that the tail risk spillover of banking industry is the largest.…”
Section: Volatility Spillover Effectsmentioning
confidence: 99%